Isolation of Indigenous Fungi in River Containing Ammonia from Rubber Industry Waste in Jember - Dwi Nur Rikhma Sari; Septarini Dian Anitasari (Pandawa Institute, 2022)
Indigenous fungi are fungi that can degrade organic compounds and make them a source of nutrition for metabolism and life so that they can to survive in various environments including environments polluted by ammonia waste from the rubber factory industry. This study was conducted to obtain fungal isolates that can survive in river water contaminated with ammonia from rubber industry waste in Jember. Isolation was obtained from river water contaminated with rubber factory waste containing ammonia and isolated using the media of Potatoes Dextrose Agar (PDA). The method used in this research is descriptive exploration, namely isolating and culturing fungi using the dilution method. The results of the isolation will identify the genus of fungi based on macroscopic and microscopic morphological characters. Data analysis was done descriptively. The results obtained 4 isolates of indigenous fungi that can degrade ammonia, namely Aspergillus sp., Fusarium sp., Penicillium sp., and Yeast groups.